ECCO Essential Requirements for Quality Cancer Care: Prostate cancer. (April 2020) - Brausi, Maurizio; Hoskin, Peter; Andritsch, Elisabeth; Banks, Ian; Beishon, Marc; Boyle, Helen; Colecchia, Maurizio; Delgado-Bolton, Roberto; Höckel, Michael; Leonard, Kay; Lövey, József; Maroto, Pablo; et al.
Highlights: ECCO Essential Requirements for Quality Cancer Care (ERQCC) are position papers on delivering high-quality care. Each paper focuses on a cancer type, in this case prostate cancer. Prostate cancer is a major healthcare burden and has complex treatment options. High-quality care can only be a carried out in specialised units or centres. The essential, multidisciplinary details for such centres are set out by the ERQCC expert group. Abstract: Background: ECCO Essential Requirements for Quality Cancer Care (ERQCC) are written by experts representing all disciplines involved in cancer care in Europe. They give oncology teams, patients, policymakers and managers an overview of essential care throughout the patient journey. Prostate cancer: Prostate cancer is the second most common male cancer and has a wide variation in outcomes in Europe. It has complex diagnosis and treatment challenges, and is a major healthcare burden. Care must only be a carried out in prostate/urology cancer units or centres that have a core multidisciplinary team (MDT) and an extended team of health professionals. Such units are far from universal in European countries. To meet European aspirations for comprehensive cancer control, healthcare organisations must consider the requirements in this paper, paying particular attention to multidisciplinarity and patient-centred pathways from diagnosis, to treatment, to survivorship.